2023
DOI: 10.1097/bpo.0000000000002458
|View full text |Cite
|
Sign up to set email alerts
|

The Perils of Sleeper Plates in Multiple Hereditary Exostosis: Tibial Deformity Overcorrection Due to Tether at Empty Metaphyseal Hole

Abstract: Background: Hemi-epiphysiodesis is the mainstay of treatment for angular deformities at the knee in children with multiple hereditary exostosis (MHE). Upon deformity correction, the metaphyseal screw may be removed from the hemi-epiphysiodesis plate, the sleeper plate technique, with anticipated reimplantation of the metaphyseal screw should the original deformity recur. The aim of the present study is to compare the incidence of complications with the sleeper plate technique with complete plate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…If only metaphyseal screws are removed, close follow-up is required. But Retzky[ 60 ] indicated that Sleeper plates technique should be avoided to use in patients with proximal tibia MHE, surgeons should be extreme caution when considering this technique.…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…If only metaphyseal screws are removed, close follow-up is required. But Retzky[ 60 ] indicated that Sleeper plates technique should be avoided to use in patients with proximal tibia MHE, surgeons should be extreme caution when considering this technique.…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…An interesting study of sleeper plates used for the treatment of proximal tibial deformity in multiple hereditary exostosis found osseous overgrowth and tethering resulting in progressive deformity overcorrection 21 . However, none of the sleeper plates used on the distal femur to treat similar deformity exhibited this phenomenon.…”
Section: Lower Extremitymentioning
confidence: 99%
“…T H E J O U R N A L O F B O N E & JOINT SURGERY d J B J S . O R G VOLUME 106-A d NUMBER 4 d F E B RUA RY21, 2024 …”
mentioning
confidence: 99%